Efektivitas Pengembangan Lembar Essay Assessment Berbasis Creative Problem Solving (CPS) untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik dalam Pembelajaran Fisika di SMA - ulmi, fauziah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Research on the development of Creative Problm Solving (CPS) based assessment essays using 4-D models. The stages in the 4-D model consist of define, design, development and disseminate. The results of the analysis from the define stage state that students' creative thinking abilities at SMAN 7 Padang are still low and the development of creative problem-based assessment essay sheets is needed. The next step to do is the design stage. The design is done to get the foundation and conformity of the development of assessment essays with the needs and characteristics of students. The next stage is the stage of development (development) which includes tests of validity, practicality, and effectiveness testing. The validation stage shows the results that the Essay assessment sheet is valid for testing. After the Essay assessment sheet is declared valid by the validator, the next step is to conduct a trial to find out its practicality and effectiveness. The effectiveness of the use of assessment essay sheets seen during limited trials is carried out. The effectiveness of assessment essays is not only seen from the improvement of students' creative thinking abilities, but also from the competencies of attitudes, knowledge, and skills. The results showed that assessment essay sheets based on creative problem solving models were developed effectively to improve students' creative thinking skills (73.08), attitude competence (83.82), and skills competencies (78.93) in learning physics.